2015
DOI: 10.1371/journal.pone.0118578
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of MATE Genes Involved in Flavonoid Transport in Blueberry Plants

Abstract: Multidrug and toxic compound extrusion (MATE) proteins are the most recently identified family of multidrug transporters. In plants, this family is remarkably large compared to the human and bacteria counterpart, highlighting the importance of MATE proteins in this kingdom. Here 33 Unigenes annotated as MATE transporters were found in the blueberry fruit transcriptome, of which eight full-length cDNA sequences were identified and cloned. These proteins are composed of 477–517 residues, with molecular masses ~5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 56 publications
3
42
0
Order By: Relevance
“…The pI values of the predicted proteins were varied in both of the cotton genomes: in G. raimondii , the pI values ranged from 4.59 to 9.5 (for example, GrMATE39 had a pI value of 4.59, whereas GrMATE65 had a pI value of 9.5), and in G. arboreum , the pI values ranged from 5 to 9.53 (the lowest pI value was obtained for GaMATE10, with a pI value of 5, whereas GaMATE8 had the highest pI value of 9.53). The results were in agreement with previous reports on the identification and expression analysis of MATE genes in blueberry plants ( Chen et al 2015 ). WoLF PSORT was used to predict the subcellular location of the various MATE proteins.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The pI values of the predicted proteins were varied in both of the cotton genomes: in G. raimondii , the pI values ranged from 4.59 to 9.5 (for example, GrMATE39 had a pI value of 4.59, whereas GrMATE65 had a pI value of 9.5), and in G. arboreum , the pI values ranged from 5 to 9.53 (the lowest pI value was obtained for GaMATE10, with a pI value of 5, whereas GaMATE8 had the highest pI value of 9.53). The results were in agreement with previous reports on the identification and expression analysis of MATE genes in blueberry plants ( Chen et al 2015 ). WoLF PSORT was used to predict the subcellular location of the various MATE proteins.…”
Section: Resultssupporting
confidence: 93%
“…A number of genome-wide studies and expression analyses of MATE genes have been conducted in soya bean ( Liu et al 2016 ), blueberry ( Chen et al 2015 ), Zea mays ( Zhu et al 2016 ), and other plants, but no work has been reported on diploid cotton to date, despite multiple studies on MATE gene families. Cotton is considered to be the foremost important natural fiber crop and is the textile industry’s most indispensable raw material globally ( Chakravarthy et al 2012 ; Zhou et al 2014 ).…”
mentioning
confidence: 99%
“…Despite tonoplast, participation of MATE proteins on flavonoid transport across PM has not been reported yet. In the case of Vaccinium corymbosum, several VcMATEs were identified as possible transporters due to their similarity with some known transporters from this family [62]. Therefore, decreased genistein and daidzein content in the NM could indicate MATE protein involving ( Figure 2).…”
Section: Transport Of Isoflavones Across Membranesmentioning
confidence: 99%
“…However, in plants this family is remarkably large signifying its importance. Arabidopsis genome encodes 58 members of the MATE family and 57 in V. vinifera, 58 in Populus trichocarpa, and 38 in Zea mays and Brachypodium distachyon (Chen et al 2015). MATEs govern diverse physiological functions in the plants such as plant growth, development and stress responses, which need to be elucidated in detail (Tiwari et al 2014).…”
Section: Mate (Multidrug and Toxic Compound Extrusion)mentioning
confidence: 99%